Marginality and the 'state of exception' in camps in Tamil Nadu. (2016) - Chowdhory, Nasreen
The paper explores the dynamics of the 'state of exception' in refugee camps in Tamil Nadu, India. Drawing on field work during 2013-14, in different districts of Tamil Nadu, i.e., Madurai, Thoothukudi, Villipuram, Coimbatore, Tirunevelli, Perrumballur, Dharmapuri, Thirupur, Krishnagiri and Sivagangai, the paper analyses the refugee households to address the question of marginality while contesting the state of exceptionality in camps. Further, it interrogates the state of exception in everyday lives of refugees. The paper asserts that the institutional policies of the government to provide assistance to refugees, and social welfare schemes, inadvertently have had a positive impact on female refugees in the camps. The data suggest that women refugees have shown curious adaptability and resilience vis-à-vis policies of state to address their needs.